2023
DOI: 10.1002/mds.29565
|View full text |Cite
|
Sign up to set email alerts
|

Differential Implications of Cerebral Hypoperfusion and Hyperperfusion in Parkinson's Disease

Seong Ho Jeong,
Su Hong Kim,
Chan Wook Park
et al.

Abstract: BackgroundPatients with Parkinson's disease (PD) exhibit widespread brain perfusion changes.ObjectiveThis study investigated whether cerebral regions with hypoperfusion and hyperperfusion have differential effects on motor and cognitive symptoms in PD using early‐phase 18F‐N‐(3‐fluoropropyl)‐2β‐carboxymethoxy‐3β‐(4‐iodophenyl) nortropane (18F‐FP‐CIT) positron emission tomography (PET) scans.MethodsWe enrolled 394 patients with newly diagnosed PD who underwent dual‐phase 18F‐FP‐CIT PET scans. Indices reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Further, it has been reported that compared to healthy controls, PD patients show vascular abnormalities and reduced perfusion 23 . Additionally, chronic cerebral hypoperfusion has been identified as a risk factor for the exacerbation of symptoms such as memory decline and motor dysfunction in PD patients 31 , 32 . In other words, hypoperfusion, which is implicated in the onset of NAION, can act as a major risk factor in the onset and progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been reported that compared to healthy controls, PD patients show vascular abnormalities and reduced perfusion 23 . Additionally, chronic cerebral hypoperfusion has been identified as a risk factor for the exacerbation of symptoms such as memory decline and motor dysfunction in PD patients 31 , 32 . In other words, hypoperfusion, which is implicated in the onset of NAION, can act as a major risk factor in the onset and progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that early-phase 18 F-N-(3fluoropropyl)-2β-carboxymethoxy-3β-(4-iodophenyl) nortropane ( 18 F-FP-CIT) PET images, which are acquired within the first 10 min after injection in a single PET session when diagnosing PD, can provide information on regional cerebral perfusion, which is closely coupled to cerebral metabolism in dopamine-poor brain regions and resembles 18 F-fluorodeoxyglucose ( 18 F-FDG) PET images. 12,13 In the present study, we investigated whether patterns of cerebral perfusion on early-phase 18 F-FP-CIT PET images have the potential to serve as a neuroimaging predictor for early dementia conversion (ie, within a 5-year time window) 7,14 in patients with newly diagnosed PD. A linear discriminant analysis (LDA) was additionally performed to develop a prediction model for PDD conversion based on regional cerebral perfusion.…”
mentioning
confidence: 99%